A combined experimental and theoretical study of the structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 - Jana, Manoj K.; Singh, Anjali; Late, Dattatray J.; Rajamathi, Catherine R.; Biswas, Kanishka; Felser, Claudia; Waghmare, Umesh V.; Rao, C. N. R. (Journal of Physics: Condensed Matter, 2015)
The recent discovery of non-saturating giant positive magnetoresistance has aroused much interest in Td-WTe2. We have investigated structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 experimentally and theoretically. Spin-orbit coupling is found to govern the semi-metallic character of Td-WTe2 and its structural link with the metallic 1 T form provides an understanding of its structural stability. There is a metal-to-insulator switch-over in the electrical conductivity and a change in the sign of the Seebeck coefficient around 373 K. Lattice vibrations of Td-WTe2 have been analyzed using first-principles calculations. Out of the 33 possible zone-center Raman active modes, five distinct Raman bands are observed around 112, 118, 134, 165 and 212 cm-1 in bulk Td-WTe2. Based on symmetry analysis and calculated Raman tensors, we assign the intense bands at 165 cm-1 and 212 cm-1 to the and modes, respectively. Most of the Raman bands stiffen with decreasing thickness, and the ratio of the integrated intensities of the to bands decreases in the few-layer sample, while all the bands soften in both the bulk and few-layer samples with increasing temperature.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Raman spectroscopy; Td-structure; tungsten ditelluride